Global restructuring, labour and the challenges for transnational solidarity (London, 2010)
"This volume examines the possibilities and obstacles to transnational solidarity in a period of global restructuring. It brings together a range of international and transnational case studies, examining successful and failed transnational solidarity covering inter-trade union co-operation as well as co-operation between trade unions and social movements within the formal and informal economy, and the public and private sector."